Proceeding of 5th Libyan Conference on Medical and Pharmaceutical Sciences 2021: ORGANIZED BY. Center of Scientific Research and International Cooperation - University of Tripoli Alahlia - Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2021)
5TH LIBYAN CONFERENCE ON MEDICAL AND PHARMACEUTICAL SCIENCES 2021 12 June, 2021 in Janzur, Libya Sponsored by the University of Tripoli Alahlia, Libya. Organizers. Dr. Ahmed Atia and Prof. Nagib Elmarzugi The 2021 5th Libyan Conference on Medical and Pharmaceutical Sciences (5th LCMPS 2021) will be held in 12 June, 2021 in Janzur, Libya. 5th LCMPS 2021 is to bring together innovative academics and industrial experts in the field of Medical and Pharmaceutical Science to a common forum. MAIN SPEAKERS. Prof. Othman Elzentani, department of Forensic Medicine Ministry of Justice, Libya. Prof. Adel Abushoffa, department of Pharmaceutical Chemistry, University of Tripoli Prof. Abdussalam Amara, department of Pharmaceutics, University of Tripoli. Dr. Hesham Ben Massaud, Emergency Medicine Consultant at Libyan Board of Medical Specialties. Conference Date: 12-06-2020. Contact: Phone: 00218910737929 - WEBSITE: https:/utripoli.edu.ly/event/5th-lcmps-2021/ - EMAIL: research.utripoli@gmail.com